2022
DOI: 10.1371/journal.pone.0271566
|View full text |Cite
|
Sign up to set email alerts
|

Examining the role of information integration in the continued influence effect using an event segmentation approach

Abstract: Misinformation regarding the cause of an event often continues to influence an individual’s event-related reasoning, even after they have received a retraction. This is known as the continued influence effect (CIE). Dominant theoretical models of the CIE have suggested the effect arises primarily from failures to retrieve the correction. However, recent research has implicated information integration and memory updating processes in the CIE. As a behavioural test of integration, we applied an event segmentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…Following a failure of Sanderson et al (2022) to find any obvious effect of boundaries in the expected direction on susceptibility to misinformation, rather than investigating the potential effects of temporal event segmentation on information integration and continued influence in a CIE paradigm, the present research aimed to reproduce previously reported effects of temporal event boundaries on memory directly. In order to achieve this, we manipulated the presence of temporal event boundaries, and measured how event boundaries affected participants' memory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a failure of Sanderson et al (2022) to find any obvious effect of boundaries in the expected direction on susceptibility to misinformation, rather than investigating the potential effects of temporal event segmentation on information integration and continued influence in a CIE paradigm, the present research aimed to reproduce previously reported effects of temporal event boundaries on memory directly. In order to achieve this, we manipulated the presence of temporal event boundaries, and measured how event boundaries affected participants' memory.…”
Section: Discussionmentioning
confidence: 99%
“…This paper follows from a previous study by Sanderson et al (2022), which investigated the effect of spatial event segmentation boundaries on information integration and updating in a continued influence effect (CIE) paradigm. The continued influence effect refers to the finding that people often continue to rely on misinformation in their eventrelated reasoning, even after the information has been retracted.…”
Section: Forewordmentioning
confidence: 99%
See 1 more Smart Citation